1989
DOI: 10.1016/0092-8674(89)90047-0
|View full text |Cite
|
Sign up to set email alerts
|

EGF induces tyrosine phosphorylation of phospholipase C-II: A potential mechanism for EGF receptor signaling

Abstract: Binding of EGF to cells expressing human EGF receptor stimulated rapid tyrosine phosphorylation of phospholipase C-II (PLC-II), as revealed by immunoblotting analysis with phosphotyrosine-specific antibodies. Tyrosine phosphorylation of PLC-II was stimulated by low physiological concentrations of EGF (1 nM), was quantitative, and was already maximal after a 30 sec incubation with 50 nM EGF at 37 degrees C. Interestingly, antibodies specific for PLC-II were able to coimmunoprecipitate the EGF receptor and antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
362
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 773 publications
(374 citation statements)
references
References 32 publications
11
362
1
Order By: Relevance
“…hydrolysis strengthens the hypothesis that the phosphorylation of PLC-II by EGFR leads to its activation [ 13,141. These studies as well as our previous reports [13,17,18,23] demonstrate the usefulness of tyrphostins as molecular tools for the dissection of the signals triggered by protein tyrosin kinases.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…hydrolysis strengthens the hypothesis that the phosphorylation of PLC-II by EGFR leads to its activation [ 13,141. These studies as well as our previous reports [13,17,18,23] demonstrate the usefulness of tyrphostins as molecular tools for the dissection of the signals triggered by protein tyrosin kinases.…”
Section: Discussionsupporting
confidence: 83%
“…The link between the EGFR and the phosphoinositide pathway was also suggested from studies on the kinase deficient mutant of the receptor. A point mutation at the ATP-binding site which nullifies the PTK activity of the receptor also abolishes the EGF-induced formation of inositol phosphates 1121, Indeed, Margolis et al [13] described the phosphorylation of PLC-II in response to EGF and proposed that this event might enhance the enzymatic activity of PLC and concluded that the EGF-induced tyrosine phosphorylation of PLC-II might be an important regulatory link between the kinase activity of the EGF receptor and the hydrolysis of PIP2. Meisenhelder et al [14] have described the phosphorylation of PLC-II (PLC y) in response to PDGF and EGF and also proposed that phosphorylation of PLC-II (PLC y) by PDGF and EGF receptors leads to its activation and to a consequent increase in PIP2 turnover.…”
Section: Introductionmentioning
confidence: 99%
“…Four sites of tyrosine phosphorylation in PLC-y have been identified [9, lo]. In addition, EGF and PDGF receptors, when stimulated by ligands, bind tightly to and coimmunoprecipitate with PLC-y [5][6][7][8]11,12]. These results suggest that PLC-y, which exists mainly (> 80%) in HER 14 cells 1131, which were derived from NIH 3T3 clone 2.2 by transfecting with human EGF receptor DNA constructs, were generously provided by Dr. J. Schlessinger (Rorer Biotechnology, Inc., King of Prussia, PA).…”
Section: Methodsmentioning
confidence: 99%
“…1A, lower panel). As a comparison, we studied tyrosine phosphorylation of phospholipase C-␥ and p120 Ras-GAP, which are two previously identified substrates for the EGF receptor kinase (35,36). Tyrosine phosphorylation of these proteins increased in a dosedependent manner in response to EGF stimulation, with no bell-shaped dose response curve; results for p120 Ras-GAP are shown in Fig.…”
Section: Tyrosine Phosphorylation Of Cas Exhibits a Bell-shaped Dosementioning
confidence: 99%